Surface-treated copper foil, copper-clad laminate, and printed wiring board

By forming a specific heteroaromatic compound layer on the surface of the copper foil and controlling its Ssk range, the problem of increased manufacturing time and cost of surface-treated copper foil is solved, and the adhesion with the resin substrate is improved, and it is particularly suitable for high-frequency applications.

CN119546801APending Publication Date: 2025-02-28JX NIPPON MINING & METALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380053761.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-29
Filing Date
2023-09-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art has problems with increasing manufacturing time and cost when surface treatment of copper foils, and in low dielectric materials, the anchoring effect of coarse particles cannot ensure sufficient adhesion, especially in high-frequency applications.

Method used

By forming a layer containing a specific heteroaromatic compound on at least one surface of the copper foil, the Ssk is controlled to be in the range of -2.00 to -0.10 to improve the adhesion with the resin substrate.

Benefits of technology

While reducing manufacturing time and cost, the adhesion between the resin substrate and the surface-treated copper foil is improved, especially in high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546801A_ABST
    Figure CN119546801A_ABST
Patent Text Reader

Abstract

The present invention relates to a surface-treated copper foil comprising a copper foil and a heteroaromatic compound layer formed on at least one surface of the copper foil. The heteroaromatic compound layer contains a heteroaromatic compound having a heterocyclic ring containing a nitrogen atom as a heteroatom, and Ssk is-2.00 to-0.10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface treated copper foil, a copper clad laminate and a printed circuit board. Background Art

[0002] Copper clad laminates are widely used in various applications such as flexible printed wiring boards. Flexible printed wiring boards are manufactured by etching the copper foil of a copper clad laminate to form a conductor pattern (also called a "circuit pattern"), and assembling electronic components by connecting them to the conductor pattern with solder.

[0003] In recent years, in electronic devices such as personal computers and mobile terminals, as communication speeds and capacities increase, electrical signals have become increasingly high-frequency, and flexible printed circuit boards that can adapt to this are needed. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of the signal power, and the more likely it is that data cannot be read, so it is required to reduce the loss of signal power.

[0004] The causes of signal power loss (transmission loss) in electronic circuits can be roughly divided into two types: conductor loss, which is the loss caused by copper foil, and dielectric loss, which is the loss caused by the resin base material.

[0005] Conductor loss has the following characteristics, that is, there is a skin effect in the high frequency band, and the current flows on the surface of the conductor. Therefore, if the surface of the copper foil is rough, the current will flow along a complex path. Therefore, in order to reduce the conductor loss of high-frequency signals, it is more ideal to reduce the surface roughness of the copper foil. Hereinafter, in this specification, when only "transmission loss" and "conductor loss" are recorded, it mainly means "transmission loss of high-frequency signals" and "conductor loss of high-frequency signals".

[0006] Dielectric loss depends on the type of resin substrate. Therefore, in a circuit board where high-frequency signals flow, it is desirable to use a resin substrate made of a low-dielectric material (eg, liquid crystal polymer, low-dielectric polyimide).

[0007] In order to ensure the adhesion between the copper foil and the resin substrate, it is proposed to form a surface treatment layer containing roughened particles on at least one surface of the copper foil. This is intended to improve the adhesion by utilizing the anchoring effect of the roughened particles immersed in the resin substrate. For example, Patent Document 1 proposes the following method: a roughened treatment layer formed of roughened particles is provided on the copper foil, and an antirust treatment layer is formed thereon. The antirust treatment layer is composed of a nickel-cobalt alloy plating layer, a zinc plating layer, a chromate treatment layer, and a silane coupling treatment layer.

[0008] Background Art Literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2012-112009 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The surface treated copper foil described in Patent Document 1 has the problem of increasing the time and cost required for its production because many layers must be formed on the copper foil. In addition, sufficient adhesion may not be ensured by the anchoring effect of the roughened particles in resin substrates, especially low dielectric materials.

[0013] The embodiment of the present invention is completed to solve the above-mentioned problems. In one aspect, the purpose is to provide a surface-treated copper foil that can reduce the time and cost required for manufacturing and improve the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications.

[0014] In another aspect, an embodiment of the present invention aims to provide a copper-clad laminate having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil while reducing the time and cost required for production.

[0015] Furthermore, in another aspect, an embodiment of the present invention aims to provide a printed wiring board that reduces the time and cost required for manufacturing and has excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a circuit pattern.

[0016] Technical means of solving problems

[0017] After intensive research to solve the above problems, the inventors surprisingly obtained the following insights: specific heteroaromatic compounds have the function of improving adhesion to resin substrates. Based on this insight, it was found that the above problems can be solved by forming a heteroaromatic compound layer containing a specific heteroaromatic compound on at least one surface of a copper foil and controlling the Ssk of the surface within a specified range, thereby completing the embodiment of the present invention.

[0018] That is, an embodiment of the present invention, in one aspect, relates to a surface-treated copper foil, comprising a copper foil and a heteroaromatic compound layer formed on at least one surface of the copper foil, wherein the heteroaromatic compound layer contains a heteroaromatic compound and has an Ssk of -2.00 to -0.10, and the heteroaromatic compound has a heterocycle containing a nitrogen atom as a heteroatom.

[0019] In another aspect, an embodiment of the present invention relates to a copper-clad laminate including the surface-treated copper foil and a resin substrate having the heteroaromatic compound layer attached to the surface-treated copper foil.

[0020] Furthermore, in another aspect, an embodiment of the present invention relates to a printed wiring board including a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.

[0021] Effects of the Invention

[0022] According to an embodiment of the present invention, in one aspect, a surface-treated copper foil can be provided that can reduce the time and cost required for production and improve adhesion to a resin substrate, particularly a resin substrate suitable for high-frequency applications.

[0023] According to an embodiment of the present invention, in another aspect, a copper-clad laminate can be provided which reduces the time and cost required for production and has excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil.

[0024] Furthermore, according to an embodiment of the present invention, in another aspect, a printed wiring board can be provided which reduces the time and cost required for production and has excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a circuit pattern. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1 ] is an example of a loading curve for a heteroaromatic compound layer. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present invention are described in detail below, but the present invention should not be limited to these for interpretation. Various changes and improvements can be made based on the knowledge of those skilled in the art without departing from the gist of the present invention. The multiple components disclosed in the following embodiments can form various inventions by appropriate combination. For example, some components can be deleted from all the components disclosed in the following embodiments, and the components of different embodiments can also be appropriately combined.

[0027] The surface-treated copper foil according to the embodiment of the present invention includes a copper foil and a heteroaromatic compound layer formed on at least one surface of the copper foil.

[0028] The heteroaromatic compound layer may be formed on only one surface of the copper foil or on both surfaces of the copper foil. When the heteroaromatic compound layer is formed on both surfaces of the copper foil, the types of the heteroaromatic compound layers may be the same or different.

[0029] The copper foil is not particularly limited, and may be either an electrolytic copper foil or a rolled copper foil.

[0030] As the material of the copper foil, high-purity copper such as refined copper (JIS H3100 alloy number C1100) or oxygen-free copper (JIS H3100 alloy number C1020 or JIS H3510 alloy number C1011) which is generally used as a circuit pattern of a printed wiring board can be used. In addition, copper alloys such as Sn-doped copper, Ag-doped copper, copper alloys added with Cr, Zr or Mg, and Casson-type copper alloys added with Ni and Si can also be used. In addition, in this specification, the so-called "copper foil" is a concept that also includes copper alloy foil.

[0031] The thickness of the copper foil is not particularly limited, and may be, for example, 1 to 1000 μm, 1 to 500 μm, 1 to 300 μm, 3 to 100 μm, 5 to 70 μm, 6 to 35 μm, or 9 to 18 μm.

[0032] The heteroaromatic compound layer contains a heteroaromatic compound having a heterocyclic ring containing a nitrogen atom as a heteroatom.

[0033] The number of ring members of the heterocyclic ring is not particularly limited, and is, for example, 3 to 9, preferably 4 to 6, and more preferably 5.

[0034] The heteroatom contained in the heterocyclic ring may consist of only nitrogen atoms, or may consist of nitrogen atoms and atoms other than nitrogen atoms (for example, oxygen atoms, sulfur atoms, etc.).

[0035] The number of heteroatoms contained in the heterocyclic ring is determined according to the number of ring members, and is, for example, 1 to 5, preferably 1 to 4, and more preferably 1 to 3.

[0036] The heterocyclic ring may be any of a saturated ring and an unsaturated ring. Here, the unsaturated ring is a concept including a partially unsaturated ring.

[0037] Specific examples of heterocyclic rings include acridine (an unsaturated three-membered ring containing one nitrogen atom), diazolinone (an unsaturated three-membered ring containing two nitrogen atoms), azolidine (an unsaturated four-membered ring containing one nitrogen atom), diazolidine (an unsaturated four-membered ring containing two nitrogen atoms), pyrrole (an unsaturated five-membered ring containing one nitrogen atom), pyrrolidine (a saturated five-membered ring containing one nitrogen atom), imidazole and pyrazole (an unsaturated five-membered ring containing two nitrogen atoms), imidazolidine and pyrazolidine (a saturated five-membered ring containing two nitrogen atoms), oxazole and isoxazole (an unsaturated five-membered ring containing one nitrogen atom and one oxygen atom), oxazolidine and isoxazolidine (a saturated five-membered ring containing one nitrogen atom and one oxygen atom), thiazole and isothiazole (unsaturated 5-membered ring containing 1 nitrogen atom and 1 sulfur atom), tetrahydrothiazole and isothiazole (saturated 5-membered ring containing 1 nitrogen atom and 1 oxygen atom), triazole such as 1,2,3-triazole or 1,2,4-triazole (unsaturated 5-membered ring containing 3 nitrogen atoms), tetrazole (unsaturated 5-membered ring containing 4 nitrogen atoms), pentazole (unsaturated 5-membered ring containing 5 nitrogen atoms), furazan and oxadiazole (unsaturated 5-membered ring containing 2 nitrogen atoms and 1 oxygen atom), thiadiazole (unsaturated 5-membered ring containing 2 nitrogen atoms and 1 sulfur atom), dioxazole (unsaturated 5-membered ring containing 1 nitrogen atom and 2 oxygen atoms), dithiazole (unsaturated 5-membered ring containing 1 nitrogen atom and 2 sulfur atoms) 1-membered ring), oxatetrazole (unsaturated 5-membered ring containing 4 nitrogen atoms and 1 oxygen atom), thiatetrazole (unsaturated 5-membered ring containing 4 nitrogen atoms and 1 sulfur atom), pyridine (unsaturated 6-membered ring containing 1 nitrogen atom), piperidine (saturated 6-membered ring containing 1 nitrogen atom), diazine (unsaturated 6-membered ring containing 2 nitrogen atoms), piperazine (saturated 6-membered ring containing 2 nitrogen atoms), oxazine (unsaturated 6-membered ring containing 1 nitrogen atom and 1 oxygen atom), phenoxylate (saturated 6-membered ring containing 1 nitrogen atom and 1 oxygen atom), thiazine (unsaturated 6-membered ring containing 1 nitrogen atom and 1 sulfur atom), thioline (saturated 6-membered ring containing 1 nitrogen atom and 1 sulfur atom), triazine (unsaturated 6-membered ring containing 3 nitrogen atoms), unsaturated 6-membered ring containing 4 nitrogen atoms), tetrazine (unsaturated 6-membered ring containing 4 nitrogen atoms), pentazine (unsaturated 6-membered ring containing 5 nitrogen atoms), azapine (unsaturated 7-membered ring containing 1 nitrogen atom), azepane (saturated 7-membered ring containing 1 nitrogen atom), diazepane (unsaturated 7-membered ring containing 2 nitrogen atoms), diazepane (saturated 7-membered ring containing 2 nitrogen atoms), azacyclooctatetraene (unsaturated 8-membered ring containing 1 nitrogen atom), azacyclooctane (saturated 8-membered ring containing 1 nitrogen atom), azonine (unsaturated 9-membered ring containing 1 nitrogen atom), azanonane (saturated 9-membered ring containing 1 nitrogen atom), etc.Among these, from the viewpoint of stably improving the adhesion to the resin substrate, the heterocyclic ring is preferably a 5-membered ring containing 1 to 3 nitrogen atoms, and more preferably an unsaturated 5-membered ring containing 1 to 3 nitrogen atoms (pyrrole, imidazole, pyrazole, oxazole, isoxazole, thiazole, isothiazole, triazole).

[0038] The heteroaromatic compound having a heterocyclic ring may be a condensed ring compound of a benzene ring and a heterocyclic ring, a condensed ring compound of two or more heterocyclic rings, or a monocyclic compound of a heterocyclic ring.

[0039] The condensed ring compound of a benzene ring and a heterocyclic ring is not particularly limited, and examples thereof include indole, indazole, isoindole, benzimidazole, benzotriazole, quinoline, isoquinoline, quinazoline, quinoxaline, cinnoline, acridine, and carbazole.

[0040] The fused ring compound of two or more heterocyclic rings is not particularly limited, and examples thereof include triazolopyridine, purine, and pteridine.

[0041] The heterocyclic monocyclic compound is not particularly limited, and the compounds exemplified above as the heterocyclic ring may be mentioned.

[0042] Furthermore, the condensed ring compound and the monocyclic compound may also have a substituent. The substituent is not particularly limited. Examples of the substituent include alkyl groups such as methyl and ethyl, vinyl groups, and nitro groups.

[0043] The heteroaromatic compound layer is a layer containing the above-mentioned heteroaromatic compound.

[0044] The heteroaromatic compound contained in the heteroaromatic compound layer may be a single type or two or more different types.

[0045] Furthermore, the heteroaromatic compound layer may contain components other than the heteroaromatic compound within a range that does not impair the effects achieved by the embodiments of the present invention. Examples of such components include solvents and additives mixed when forming the heteroaromatic compound layer.

[0046] Compared with the previous surface treatment layer including the roughening treatment layer, the peak of the heteroaromatic compound layer is less. That is, the smoothness of the heteroaromatic compound layer is high. The reason is that the previous surface treatment layer including the roughening treatment layer is to improve the adhesion between the surface treatment layer and the resin substrate by the anchoring effect, and the heteroaromatic compound layer is not intended to obtain the adhesion improvement effect brought by the anchoring effect. That is, the heteroaromatic compound layer is to improve the adhesion between the surface-treated copper foil and the resin substrate by the adhesion characteristics of the heteroaromatic compound, so even if the peak and valley of the surface are few, the desired adhesion improvement effect can be obtained. In addition, the heteroaromatic compound layer is compared with the previous surface treatment layer including the roughening treatment layer, because the surface smoothness is high, it is possible to reduce the transmission loss caused by the skin effect.

[0047] As one of the indicators representing the smoothness of the surface, Ssk (skewness), which is an indicator representing the distribution of peaks and valleys of the surface, can be used. Ssk is a parameter in the height direction specified by ISO 25178-2:2012, which represents the symmetry of the peaks and valleys relative to the average surface of the surface. When Ssk is 0, it means that the peaks and valleys are symmetrically distributed. In addition, if Ssk is greater than 0, it means that the peaks of the surface are more than the valleys, and if Ssk is less than 0, it means that the valleys of the surface are more than the peaks.

[0048] The Ssk of the heteroaromatic compound layer is -2.00 to -0.10. That is, the surface of the heteroaromatic compound layer has more valleys than peaks. Since the surface treatment layer including the roughening treatment layer has many peaks, it can be said that the surface smoothness of the heteroaromatic compound layer is high. Since the heteroaromatic compound layer with Ssk controlled within this range is smooth, the adhesion between the surface treated copper foil and the resin substrate can be improved by the adhesion characteristics of the heteroaromatic compound. In addition, the effect of reducing transmission loss can also be obtained.

[0049] From the viewpoint of stably obtaining the above-mentioned effect, the Ssk of the heteroaromatic compound layer is preferably -2.00 to -0.50, more preferably -2.00 to -0.80, and still more preferably -1.50 to -0.80.

[0050] In addition, the Ssk of the heteroaromatic compound layer can be measured in accordance with ISO 25178-2:2012.

[0051] Compared to the conventional surface treatment layer including the roughening treatment layer, the heteroaromatic compound layer has fewer peaks on the surface because there are no roughening particles. As an index representing the peak ratio of the surface of such a heteroaromatic compound layer, Vmp (substantial volume of the peak) can be used. Vmp is a functional (volume) parameter specified by ISO 25178-2:2012, which represents the substantial volume of the peak of the heteroaromatic compound layer.

[0052] Vmp can be measured by measuring the surface roughness according to ISO 25178-2:2012 and analyzing the load curve calculated from the measured data.

[0053] When explaining the load curve, the load area ratio will be explained first.

[0054] The so-called load area ratio refers to the ratio obtained by dividing the area of ​​the cross section of the measured object when the three-dimensional measured object is cut at a certain height plane by the area of ​​the measured field of view. Furthermore, in the present invention, it is assumed that the copper foil or the heteroaromatic compound layer of the surface-treated copper foil is used as the measured object. The load curve is a curve showing the load area ratio at each height. The height of the highest part of the measured object is shown near the load area ratio of 0%, and the height of the lowest part of the measured object is shown near the load area ratio of 100%.

[0055] Then, Figure 1 An example of a load curve is disclosed in . The load curve can be flexibly used to represent the solid volume and space volume of the heteroaromatic compound layer. The so-called solid volume is equivalent to the volume of the part occupied by the entity of the measured object in the measurement field of view, and the so-called space volume is equivalent to the volume occupied by the space between the solid parts in the measurement field of view. In the load curve, the positions where the load area ratio is 10% and 80% are used as boundaries to divide it into valleys, cores and peaks. If referring to Figure 1 And corresponding to the heteroaromatic compound layer of the implementation scheme of the present invention, Vvv means the spatial volume of the valley part of the heteroaromatic compound layer, Vvc means the spatial volume of the core part of the heteroaromatic compound layer, Vmp means the entity volume of the peak part of the heteroaromatic compound layer, and Vmc means the entity volume of the core part of the heteroaromatic compound layer.

[0056] Furthermore, the peak is the part with high height in the object to be measured, while the valley is the part with low height in the object to be measured. The core is the part other than the peak and valley in the object to be measured, that is, the part with a height close to the average.

[0057] The substantial volume Vmp of the peak portion is the substantial volume of the peak portion, ie, the high portion of the measurement object, and means the volume of the substantial volume of the particularly high portion in the heteroaromatic compound layer.

[0058] The Vmp of the heteroaromatic compound layer is preferably 0.001 to 0.010 μm 3 / μm 2 , more preferably 0.001 to 0.006 μm 3 / μm 2The range of Vmp of the solid volume of the part with particularly high height is such a range, which means that the heteroaromatic compound layer is smooth. Moreover, by controlling Vmp in such a range, the adhesion between the surface-treated copper foil and the resin substrate can be improved due to the adhesion characteristics of the heteroaromatic compound. In addition, the effect of reducing transmission loss can also be obtained.

[0059] In addition, the Vmp of the heteroaromatic compound layer can be measured in accordance with ISO 25178-2:2012.

[0060] Compared with the surface treatment layer of the past including the roughening treatment layer, the heteroaromatic compound layer is smoother because there are no roughening particles. The valleys on the surface of this heteroaromatic compound layer are also shallower. As an indicator of the depth of the valley, Sv (the maximum valley depth of the valley) can be used. Sv is a height parameter specified by ISO 25178-2:2012, which represents the minimum value of the height from the average surface of the surface of the heteroaromatic compound layer.

[0061] The Sv of the heteroaromatic compound layer is preferably 1.50 μm or less, more preferably 0.10 to 1.25 μm, and further preferably 0.50 to 1.20 μm. By controlling the Sv in this range, the adhesion between the surface-treated copper foil and the resin substrate can be improved due to the adhesion characteristics of the heteroaromatic compound. In addition, the effect of reducing transmission loss can also be obtained.

[0062] In addition, Sv of the heteroaromatic compound layer can be measured in accordance with ISO 25178-2:2012.

[0063] The surface treated copper foil of the embodiment of the present invention is preferably in direct contact with the heteroaromatic compound layer, but a functional layer may be provided between the copper foil and the heteroaromatic compound layer within the range that does not impair the effect of the embodiment of the present invention. Examples of the functional layer include a heat resistant treatment layer, a rust-proof treatment layer, and a chromate treatment layer.

[0064] The surface-treated copper foil manufacturing method according to the embodiment of the present invention is not particularly limited, and can be manufactured by, for example, the following method.

[0065] First, copper foil is manufactured by a method known in the art. For example, when electrolytic copper foil is used as copper foil, it can be manufactured by electrolytically depositing copper on a titanium or stainless steel drum from a copper sulfate plating bath. Again, when rolled copper foil is used as copper foil, it can be manufactured by homogenizing annealing, hot rolling, cold rolling, annealing, etc. to copper ingots in sequence. Alternatively, since copper foil is commercially available, commercial products can also be used. However, when using commercial copper foil, rust inhibitors or oils are sometimes attached to the surface of the copper foil, so the copper foil is degreased and pickled. The reason is that if various surface treatment layers are formed on the surface of the copper foil, it is difficult to form a heteroaromatic compound layer on the surface of the copper foil.

[0066] Next, a coating liquid of a heteroaromatic compound is prepared. The coating liquid may contain a solvent such as water or an additive. The concentration of the heteroaromatic compound in the coating liquid may be adjusted according to the type of the heteroaromatic compound used, and is not particularly limited, and is, for example, 0.1 to 10% by mass.

[0067] Then, a heteroaromatic compound layer is formed by applying a coating liquid of a heteroaromatic compound to the surface of the copper foil and drying it. The coating method is not particularly limited, and various methods such as dipping, spraying, curtain-type flat coater coating, roller coater coating, brush coating, roller brush coating, etc. can be used. In addition, the drying method is not particularly limited, and room temperature drying or heating drying can be selected according to the type of solvent used. The coating and drying of the coating liquid of the heteroaromatic compound can be performed once, but can also be performed multiple times to form a heteroaromatic compound layer of the desired thickness.

[0068] Furthermore, the Ssk, Vmp and Sv of the heteroaromatic compound layer can be controlled mainly by adjusting the surface roughness of the copper foil forming the heteroaromatic compound layer. The roughness of the copper foil can be controlled by adjusting the manufacturing conditions of the copper foil, the degreasing conditions or the pickling conditions before the heteroaromatic compound layer is formed.

[0069] The surface-treated copper foil according to the embodiment of the present invention has a heteroaromatic compound layer containing a specific heteroaromatic compound, and the Ssk of the heteroaromatic compound layer is controlled to -2.00 to -0.10, thereby reducing the time and cost required for manufacturing and improving the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications.

[0070] A copper-clad laminate according to an embodiment of the present invention comprises the surface-treated copper foil described above and a resin substrate having a heteroaromatic compound layer attached to the surface-treated copper foil.

[0071] The copper-clad laminate can be produced by bonding a resin substrate to the heteroaromatic compound layer of the surface-treated copper foil.

[0072] As the resin substrate, there is no particular limitation, and those known in the technical field can be used. Examples of resin substrates include: paper-based phenolic resins, paper-based epoxy resins, synthetic fiber cloth-based epoxy resins, glass cloth-paper composite-based epoxy resins, glass cloth-glass non-woven composite-based epoxy resins, glass cloth-based epoxy resins, polyester films, polyimide resins, liquid crystal polymers, fluororesins, etc. Among these, the resin substrate is preferably a polyimide resin. In addition, the resin substrate can also be formed by a low dielectric material. Examples of low dielectric materials include liquid crystal polymers, low dielectric polyimides, etc.

[0073] The bonding method between the surface-treated copper foil and the resin substrate is not particularly limited, and can be carried out according to a method known in the art. For example, the surface-treated copper foil and the resin substrate may be laminated and then thermally pressed.

[0074] The copper-clad laminate produced in the above manner can be used in the production of printed wiring boards.

[0075] Since the copper-clad laminate according to the embodiment of the present invention uses the surface-treated copper foil, the time and cost required for production can be reduced and the adhesion between the resin substrate, especially the resin substrate suitable for high-frequency applications, and the surface-treated copper foil can be improved.

[0076] A printed wiring board according to an embodiment of the present invention includes a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.

[0077] The printed wiring board can be manufactured by etching the surface treated copper foil of the copper clad laminate to form a circuit pattern. The method for forming the circuit pattern is not particularly limited, and known methods such as a subtractive method and a semi-additive method can be used. Among them, the method for forming the circuit pattern is preferably a subtractive method.

[0078] When a printed circuit board is manufactured by a subtractive method, it is preferably carried out in the following manner. First, a resist is applied to the surface of the surface-treated copper foil of the copper-clad laminate, and exposure and development are performed to form a predetermined resist pattern. Then, the surface-treated copper foil of the portion where the resist pattern is not formed (the unnecessary portion) is removed by etching to form a circuit pattern. Finally, the resist pattern on the surface-treated copper foil is removed.

[0079] In addition, various conditions in the subtractive method are not particularly limited, and the method can be carried out according to conditions known in the technical field.

[0080] Since the printed wiring board according to the embodiment of the present invention uses the copper-clad laminate, the time and cost required for manufacturing can be reduced, and the adhesion between the resin substrate, especially the resin substrate suitable for high-frequency applications, and the circuit pattern can be improved.

[0081] [Example]

[0082] Hereinafter, the embodiments of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples in any way.

[0083] (Example 1)

[0084] Commercially available rolled copper foil (HA-V2 manufactured by JX Metal Co., Ltd.; thickness 12 μm) was prepared as copper foil, and both surfaces of the copper foil were degreased and pickled. Degreasing was performed in the following manner: 20 g / L GN Cleaning Liquid 87 (JX Metal Trading Co., Ltd.) aqueous solution was used at a current density of 11.3 A / dm 2 The surface of the rolled copper foil was electrolyzed under the conditions of 0.5 % and 1.5 % for 8.6 seconds. The pickling was performed by immersing in a 20 g / L sulfuric acid aqueous solution for 30 seconds.

[0085] Next, a benzotriazole solution (coating solution) was prepared using benzotriazole represented by the following formula (1) as a heteroaromatic compound. The concentration of benzotriazole in the aqueous solution was set to 1% by mass.

[0086]

[0087] Next, the copper foil was immersed in an aqueous solution of benzotriazole for 30 seconds, washed with water, and dried in a dryer. In this way, a surface-treated copper foil having a benzotriazole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained.

[0088] (Example 2)

[0089] A surface-treated copper foil having an indazole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that indazole represented by the following formula (2) was used as the heteroaromatic compound.

[0090]

[0091] (Example 3)

[0092] A surface-treated copper foil having a benzimidazole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that benzimidazole represented by the following formula (3) was used as the heteroaromatic compound.

[0093]

[0094] (Example 4)

[0095] A surface-treated copper foil having an indole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that indole represented by the following formula (4) was used as the heteroaromatic compound.

[0096]

[0097] (Example 5)

[0098] A surface-treated copper foil having a triazolopyridine layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that triazolopyridine represented by the following formula (5) was used as the heteroaromatic compound.

[0099]

[0100] (Example 6)

[0101] A surface-treated copper foil having a 1-methylbenzotriazole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that 1-methylbenzotriazole represented by the following formula (6) was used as the heteroaromatic compound.

[0102]

[0103] (Example 7)

[0104] A surface-treated copper foil having a 5-methylbenzotriazole layer (heteroaromatic compound layer) formed on the surface of the copper foil was obtained under the same conditions as in Example 1 except that 5-methylbenzotriazole represented by the following formula (7) was used as the heteroaromatic compound.

[0105]

[0106] (Example 8)

[0107] A surface-treated copper foil having a 1,2,3-triazole layer (heteroaromatic compound layer) formed on the copper foil surface was obtained under the same conditions as in Example 1 except that 1,2,3-triazole represented by the following formula (8) was used as the heteroaromatic compound.

[0108]

[0109] (Comparative Example 1)

[0110] A commercial rolled copper foil (HA-V2 manufactured by JX Metal Co., Ltd.; thickness 12 μm) was degreased and pickled on both sides (copper foil without a heteroaromatic compound layer formed) as a comparative sample. The degreasing and pickling were performed under the same conditions as in Example 1.

[0111] (Comparative Example 2)

[0112] Under the same conditions as in Example 1, both surfaces of a commercially available rolled copper foil (HA-V2 manufactured by JX Metal Co., Ltd.; thickness 12 μm) were degreased and pickled.

[0113] Then, a roughening treatment layer, a rust-proof layer, and a silane coupling treatment layer are sequentially formed on the surface of the copper foil to obtain a surface-treated copper foil. The conditions for forming each layer are as follows.

[0114] <Roughening treatment layer>

[0115] The roughening treatment layer is formed by electroplating. The electroplating is performed in three stages. The plating solution composition and current density are basically the values ​​obtained by rounding off the first decimal place.

[0116] (Conditions for Phase 1)

[0117] Plating solution composition: 11g / L Cu, 50g / L sulfuric acid

[0118] Plating solution temperature: 27°C

[0119] Electroplating conditions: current density 40A / dm 2 , time 1.4 seconds

[0120] (Conditions for Phase 2)

[0121] Plating solution composition: 20g / L Cu, 100g / L sulfuric acid

[0122] Plating solution temperature: 50°C

[0123] Electroplating conditions: current density 5A / dm 2 , time 2.0 seconds

[0124] (Conditions for Phase 3)

[0125] Plating solution composition: 16g / L Cu, 8g / L Co, 10g / L Ni

[0126] Plating solution pH: 2.4

[0127] Plating solution temperature: 36°C

[0128] Electroplating conditions: current density 32A / dm 2 , time 0.2 seconds

[0129] <Rust-proof layer>

[0130] The rust-proof layer is formed by electroplating. The electroplating is carried out in three stages.

[0131] (Conditions for Phase 1)

[0132] Plating solution composition: 3g / L Co, 13g / L Ni

[0133] Plating solution pH: 2.0

[0134] Plating solution temperature: 50°C

[0135] Electroplating conditions: current density 2A / dm 2 , time 0.8 seconds

[0136] (Conditions for Phase 2)

[0137] Plating solution composition: 5g / L Zn, 24g / L Ni

[0138] Plating solution pH: 3.6

[0139] Plating solution temperature: 40°C

[0140] Electroplating conditions: current density 4A / dm 2 , time 0.4 seconds

[0141] (Stage 3 conditions)

[0142] Plating solution composition: 3g / L K2Cr2O7, 0.3g / L Zn

[0143] Plating solution pH: 3.7

[0144] Plating solution temperature: 55°C

[0145] Electroplating conditions: current density 3A / dm 2 , time 0.8 seconds

[0146] <Silane coupling treatment layer>

[0147] A silane coupling treatment layer was formed by applying a 4.0 vol% aqueous solution (pH: 10.4) of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (KBM603 manufactured by Shin-Etsu Chemical Co., Ltd.) and drying the mixture.

[0148] (Comparative Example 3)

[0149] Under the same conditions as in Example 1, both surfaces of a commercially available rolled copper foil (HA-V2 manufactured by JX Metal Co., Ltd.; thickness 12 μm) were degreased and pickled.

[0150] Next, a roughening treatment layer, a heat-resistant layer, a chromate treatment layer, and a silane coupling treatment layer were sequentially formed on the surface of the copper foil to obtain a surface-treated copper foil. The conditions for forming each layer are as follows.

[0151] <Roughening treatment layer>

[0152] The roughening layer is formed by electroplating. The electroplating is performed in two stages.

[0153] (Conditions for Phase 1)

[0154] Plating solution composition: 11g / L Cu, 50g / L sulfuric acid

[0155] Plating solution temperature: 25°C

[0156] Electroplating conditions: current density 42.7A / dm 2 , time 1.4 seconds

[0157] (Conditions for Phase 2)

[0158] Plating solution composition: 20g / L Cu, 100g / L sulfuric acid

[0159] Plating solution temperature: 50°C

[0160] Electroplating conditions: current density 3.8A / dm 2 , time 2.8 seconds

[0161] <Heat-resistant layer>

[0162] The heat-resistant layer is formed by electroplating.

[0163] Plating solution composition: 23.5g / L Ni, 4.5g / L Zn

[0164] Plating solution pH: 3.6

[0165] Plating solution temperature: 40°C

[0166] Electroplating conditions: current density 1.1A / dm 2 , time 0.7 seconds

[0167] <Chromate treatment layer>

[0168] The chromate treatment layer is formed by electroplating.

[0169] Plating solution composition: 3.0g / L K2Cr2O7, 0.33g / L Zn

[0170] Plating solution pH: 3.6

[0171] Plating solution temperature: 50°C

[0172] Electroplating conditions: current density 2.1A / dm 2 , time 1.4 seconds

[0173] <Silane coupling treatment layer>

[0174] A 1.2 vol % aqueous solution (pH: 10) of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (KBM603 manufactured by Shin-Etsu Chemical Co., Ltd.) was applied and dried to form a silane coupling treatment layer.

[0175] The following property evaluations were performed on the surface-treated copper foils or copper foils obtained in the above-mentioned Examples and Comparative Examples.

[0176] <Ssk, Vmp and Sv>

[0177] The images were captured using a laser microscope (LEXT OLS4000) manufactured by Olympus Corporation. The captured images were analyzed using the analysis software of a laser microscope (LEXT OLS4100) manufactured by Olympus Corporation. The measurements of Ssk, Vmp, and Sv were performed in accordance with ISO 25178-2:2012. For these measurement results, the average value of the values ​​measured at any three locations was taken as the measurement result. Furthermore, the temperature during the measurement was set to 23 to 25°C. The main setting conditions in the laser microscope and the analysis software are as follows.

[0178] Objective lens: MPLAPON50XLEXT (magnification: 50x, numerical aperture: 0.95, immersion type: air, mechanical tube length: ∞, cover glass thickness: 0, field of view number: FN18)

[0179] Optical zoom ratio: 1x

[0180] Scanning mode: XYZ high precision (height resolution: 60nm, number of pixels of input data: 1024×1024)

[0181] Input image size [number of pixels]: 257 μm x 258 μm [1024 x 1024]

[0182] (Since it is measured in the horizontal direction, the evaluation length is equivalent to 257μm)

[0183] DIC: Off

[0184] Multilayer: Off

[0185] Laser Strength: 100

[0186] Offset: 0

[0187] Confocal level: 0

[0188] Beam Diameter Aperture: Closed

[0189] Image averaging: 1 time

[0190] Noise Reduction: On

[0191] Uneven brightness correction: On

[0192] Optical Noise Filter: On

[0193] Cut-off: λc=200μm, no λs and λf

[0194] Filter: Gaussian filter

[0195] Noise Removal: Pre-Assay Processing

[0196] Surface (tilt) correction: implemented

[0197] Brightness: Adjust to a range of 30 to 50

[0198] The lightness is a value that should be appropriately set according to the color tone of the measurement object. The above setting is an appropriate value when measuring the surface of the surface-treated copper foil with L* of -69 to -10, a* of 2 to 32, and b* of 2 to 21.

[0199] <Measurement of color tone of measurement object>

[0200] MiniScan (registered trademark) EZ Model 4000L manufactured by HunterLab was used as a measuring instrument, and the L*, a* and b* of the CIE L*a*b* colorimetric system were measured in accordance with JIS Z8730:2009. Specifically, the surface of the surface-treated copper foil or copper foil obtained in the above-mentioned embodiment and comparative example was pressed against the photosensitive part of the measuring instrument, and the measurement was performed without light entering from the outside. In addition, the measurement of L*, a* and b* was performed based on the geometric condition C of JIS Z8722:2009. In addition, the main conditions of the measuring instrument are as follows.

[0201] Optical system: d / 8°, integrating sphere size: 63.5mm, observation light source: D65

[0202] Measurement method: Reflection

[0203] Illumination diameter: 25.4mm

[0204] Measuring diameter: 20.0mm

[0205] Measurement wavelength, interval: 400~700nm, 10nm

[0206] Light source: Pulse xenon lamp, 1 light emission / measurement

[0207] Traceability standards: Based on CIE 44 and ASTM E259 with calibration by the National Institute of Standards and Technology (NIST)

[0208] Standard observer: 10°

[0209] In addition, the white tiles used as the measurement reference were those of the following object colors.

[0210] When measured at D65 / 10°, the values ​​in the CIE XYZ colorimetric system are X: 81.90, Y: 87.02, Z: 93.76

[0211] <Peel strength>

[0212] After the surface-treated copper foil is bonded to a resin substrate formed by a low-dielectric material, a circuit with a width of 3 mm is formed along the MD direction (the length direction of the rolled copper foil). The formation of the circuit is implemented according to the usual method. Then, the strength (MD90° peel strength) when the circuit (surface-treated copper foil) is peeled off vertically at a speed of 50 mm / min in a 90° direction relative to the surface of the resin substrate, that is, relative to the surface of the LCP substrate, is measured according to JIS C6471:1995. The measurement is performed 3 times, and its average value is used as the result of the peel strength. If the peel strength is 0.50 kgf / cm or more, it can be said that the adhesion between the circuit (surface-treated copper foil) and the LCP substrate is good.

[0213] Table 1 shows the results of the above-mentioned property evaluations.

[0214] [Table 1]

[0215]

[0216] As shown in Table 1, the surface-treated copper foils of Examples 1 to 8 in which a heteroaromatic compound layer is formed and whose Ssk is in the range of -2.00 to -0.10 have the same peel strength as the surface-treated copper foil of Comparative Example 2 in which a surface-treated layer such as a roughening treatment layer is formed, and the adhesion between the LCP substrate and the surface-treated copper foil is good.

[0217] On the other hand, the copper foil of Comparative Example 1 in which the heteroaromatic compound layer was not formed had low peel strength. In addition, it is considered that since the roughening of Comparative Example 3 was smaller than that of Comparative Example 2, the peel strength was low.

[0218] The above results are surprising. As mentioned above, the adhesion between copper foil and resin substrates such as LCP substrates is generally improved by forming a surface treatment layer containing roughened particles. In an embodiment of the present invention, the adhesion with resin substrates such as LCP substrates is fully ensured by the presence of a heteroaromatic compound layer with a smooth surface.

[0219] From the above results, it can be seen that according to an embodiment of the present invention, a surface-treated copper foil can be provided that can suppress the time and cost required for manufacturing and improve the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications. In addition, according to an embodiment of the present invention, a copper-clad laminate can be provided that suppresses the time and cost required for manufacturing and has excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil. Furthermore, according to an embodiment of the present invention, a printed wiring board can be provided that suppresses the time and cost required for manufacturing and has excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a circuit pattern.

[0220] The embodiments of the present invention may also adopt the following aspects.

[0221] <1>

[0222] A surface-treated copper foil comprises a copper foil and a heteroaromatic compound layer formed on at least one surface of the copper foil.

[0223] The heteroaromatic compound layer contains a heteroaromatic compound having a heterocyclic ring containing a nitrogen atom as a heteroatom, and has an Ssk of -2.00 to -0.10.

[0224] <2>

[0225] The surface-treated copper foil as described in the above <1>, wherein the heterocyclic ring is a 5-membered ring containing 1 to 3 nitrogen atoms.

[0226] <3>

[0227] The surface-treated copper foil as described in <1> or <2> above, wherein the heteroaromatic compound is a condensed ring compound of a benzene ring and the heterocyclic ring, a condensed ring compound of two or more heterocyclic rings, or a monocyclic compound of the heterocyclic ring.

[0228] <4>

[0229] The surface-treated copper foil as described in any one of <1> to <3> above, wherein the heteroaromatic compound is one or more selected from the group consisting of benzotriazole, indazole, benzimidazole, indole, triazolopyridine, 1-methylbenzotriazole, 5-methylbenzotriazole, and 1,2,3-triazole.

[0230] <5>

[0231] The surface-treated copper foil as described in any one of <1> to <4> above, wherein the Ssk is -2.00 to -0.50.

[0232] <6>

[0233] The surface-treated copper foil as described in the above <5>, wherein the Ssk is -2.00 to -0.80.

[0234] <7>

[0235] The surface-treated copper foil as described in the above <5>, wherein the Ssk is -1.50 to -0.80.

[0236] <8>

[0237] The surface-treated copper foil according to any one of <1> to <7>, wherein the Vmp of the heteroaromatic compound layer is 0.001 to 0.010 μm 3 / μm 2 .

[0238] <9>

[0239] The surface-treated copper foil as described in <8> above, wherein the Vmp is 0.001 to 0.006 μm 3 / μm 2 .

[0240] <10>

[0241] A copper-clad laminate comprising the surface-treated copper foil according to any one of <1> to <9>, and a resin substrate having the heteroaromatic compound layer attached to the surface-treated copper foil.

[0242] <11>

[0243] A printed wiring board comprising a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate according to <10>.

Claims

1. A surface-treated copper foil comprising a copper foil and a heteroaromatic compound layer formed on at least one surface of the copper foil, The heteroaromatic compound layer contains a heteroaromatic compound having a heterocyclic ring containing a nitrogen atom as a heteroatom, and has an Ssk of -2.00 to -0.

10.

2. The surface-treated copper foil according to claim 1, wherein The heterocyclic ring is a 5-membered ring containing 1 to 3 nitrogen atoms.

3. The surface-treated copper foil according to claim 1, wherein The heteroaromatic compound is a condensed ring compound of a benzene ring and the heterocyclic ring, a condensed ring compound of two or more heterocyclic rings, or a monocyclic compound of the heterocyclic ring.

4. The surface-treated copper foil according to claim 1, wherein The heteroaromatic compound is one or more selected from the group consisting of benzotriazole, indazole, benzimidazole, indole, triazolopyridine, 1-methylbenzotriazole, 5-methylbenzotriazole and 1,2,3-triazole.

5. The surface-treated copper foil according to claim 3, wherein The Ssk is -2.00 to -0.

50.

6. The surface-treated copper foil according to claim 3, wherein The Ssk is -2.00 to -0.

80.

7. The surface-treated copper foil according to claim 3, wherein: The Ssk is -1.50 to -0.

80.

8. The surface-treated copper foil according to any one of claims 1 to 7, wherein The Vmp of the heteroaromatic compound layer is 0.001 to 0.010 μm 3 / μm 2 .

9. The surface-treated copper foil according to claim 8, wherein: The Vmp is 0.001 to 0.006 μm 3 / μm 2 . 10 . A copper-clad laminate comprising the surface-treated copper foil according to claim 8 , and a resin substrate having the heteroaromatic compound layer attached to the surface-treated copper foil. 11 . A printed wiring board comprising a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate according to claim 10 .

Citation Information

Patent Citations

  • Copper foil, and method for producing copper foil

    JP2012112009A